RESEPSI SASTRA DAN INTERTEKSTUALITAS SEBAGAI ALTERNATIF PEMBELAJARAN EFEKTIF DALAM MATA KULIAH DRAMAANALYSIS - Hetami, Fatma (Universitas Negeri Semarang, 2010)
Compared to other literary works, drama is the most unique one. It is based on thedefinition that drama is made to be performed. For the reader, these images of actioncome to life when we interact with the combination of dialogues and stage directionswe call a script. The printed page does not make drama itself. The activating ingredientis our living response to what we read.And the two most important resources we haveas readers are our powers of imagination and empathy. Drama analysis as one of thesubjects learned in a university has become a class that is tiresome and timeconsuming.Students often do not enjoy or even understand the text. It is due to themethod of learning which focuses on the structural elements of the text. To avoid suchconstraint there are two alternative approaches provided by the writer, they are readerresponse and intertextuality. Those two methods are the combination of readers, text,and how the readers respond to the text. They can be applied as a solution of students'boredom in a drama analysis class. By using the approach of reader response andintertextuality students can enjoy the class more than before and even be able toperform all the skills of response such as describing, engaging, explaining,interpreting, connecting, as well as judging. The provided activities require thestudents to develop their sensitivity in analyzing a drama by using their imagination,empathy, sympathy, antipathy, feeling and thought.Kata Kunci : resepsi sastra, intertekstualitas, drama analysis,membaca drama